Haiti : First Review Under the Extended Credit Facility Arrangement-Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Haiti. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The economy of Haiti is recovering despite the challenging international and domestic environments. The FY2011 budget appropriately supports the reconstruction objectives in a context of sustainable public financing. Monetary policy remains geared toward keeping inflation in the single digits. The structural reform agenda continues to focus on improving the business climate and promoting private sector-led growth. International assistance is critical to recovering from the 2010 earthquake in Haiti. Reconstruction is under way, albeit at a slower pace than envisaged. The humanitarian response from donors to the earthquake was quick and sizable.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet